2018
DOI: 10.1007/s00268-018-4855-8
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity Lost? Diagnostic Laparoscopy in Patients with Pancreatic Cancer in the National Surgical Quality Improvement Program Database

Abstract: Background Routine preoperative staging in pancreas cancer is controversial. We sought to evaluate the rates of diagnostic laparoscopy (DLAP) for pancreatic cancer. Methods We queried the National Surgical Quality Improvement Program for patients with pancreas cancer (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) and compared groups who underwent DLAP, exploratory laparotomy (XLAP), pancreas resection (RSXN) or therapeutic bypass (THBP). We compared demographics, comorbidities, postoperative complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Najah et al indicated that single-incision laparoscopic peritoneal exploration could be safely applied in the management of patients with peritoneal metastases (17). Several studies have concluded that compared to laparotomy, diagnostic laparoscopy routinely used not only saves patients an incision, but also shortens the intervals between operation and adjuvant therapy (18)(19)(20). However, given the high cost, low proportion of metastasis and limited additional value, it is still controversial whether staging laparoscopy should be applied routinely or selectively (21).…”
Section: Discussionmentioning
confidence: 99%
“…Najah et al indicated that single-incision laparoscopic peritoneal exploration could be safely applied in the management of patients with peritoneal metastases (17). Several studies have concluded that compared to laparotomy, diagnostic laparoscopy routinely used not only saves patients an incision, but also shortens the intervals between operation and adjuvant therapy (18)(19)(20). However, given the high cost, low proportion of metastasis and limited additional value, it is still controversial whether staging laparoscopy should be applied routinely or selectively (21).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic laparoscopy can help to rule out previously undetected local invasion or abdominal metastases, avoid futile explorative laparotomies, and define treatment paths, especially in patients at high risk for locally advanced tumors or systemic involvement 51–53…”
Section: Introductionmentioning
confidence: 99%
“…Routine laparoscopy was not performed, and this could be a drawback of our study; we suppose that any included patients could have been spared exploration if laparoscopy was performed. However, laparoscopy is not routinely performed worldwide and a recent large series reported that about 10% of patients underwent this procedure [17]. Similarly, its relevance remains under debate.…”
Section: Discussionmentioning
confidence: 99%